[Memo from S. Stuntz to B. Adams re: Availability of 1993 Funds in PAD Budget] - SUSAN STUNTZ (Tufts Archival Research Center, 2007)
Memo from Susan Stuntz to Bill Adams regarding the availability of 1993 funds in PAD budget. Finds that more money is available for issue advertising around the date of the Surgeon General's report. Sums up true level of available funds for recruitment and training of new scientific witnesses.